General Principles and Challenges of Public Administration Organization in Poland - Modrzejewski, Artur K. (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
This chapter aims to present the functions of public administration in Poland (central and local governments). It examines the Polish public administration system, its constitutional framework, the principles of the Constitution, and the broader constitutional order that applies to public administration. The chapter analyses the conceptual position of the executive branch within the system of governmental branches in light of the constitutional order, demonstrating how public administration is fundamentally influenced by the structure of supreme constitutional organs and their interrelationships. The chapter addresses the system of relations between public administration and other state bodies (e.g. Parliament, the President of the Republic, and the Public Prosecutor’s Office). Finally, it discusses current challenges in public administration. KEYWORDS public administration in Poland, Polish constitutional order, Polish local government, conceptual position of the executive in the system in Poland, the functioning of the Polish public administration Bibliography Banasiński, C. (2009) ‘Prywatyzacja zadań publicznych w sferze gospodarki’ in Gronkiewicz-Waltz, H., Wierzbowski, M. (eds.) Prawo gospodarcze. Zagadnienia administracyjnoprawne. Warszawa: Wolters Kluwer, pp. 333–341. Bandarzewski, K. (2007) ‘Prywatyzacja zadań publicznych’ in Zimmermann, J. (ed.) Koncepcja system prawa administracyjnego. Warszawa: Wolters Kluwer, pp. 331–346. Batalli, M., Fejzullahu, A. (2008) ‘Principles of Good Administration under the European Code of Good Administrative Behavior’, Pécs Journal of International and European Law, 1, pp. 26–35. Bel, G., Gradus, R. (2017) ‘Privatisation, contracting-out and inter-municipal cooperation: new developments in local public service delivery’, Local Government Studies, 44(1), pp. 11–21 [Online]. Available at: https://doi.org/10.1080/03003930.2017.1403904 (Accessed: 12 September 2024). Biernat, S. (1994) Prywatyzacja zadań publicznych. Problematyka prawna. Warszawa–Kraków: Wolters Kluwer. Błaś, A. (2004) ‘Współczesne tendencje przeobrażeń zadań administracji publicznej’ in Boć, J., Błaś, A., Jeżewski, J. (eds.) Administracja publiczna. Wrocław: Kolonia Limited. Boć, J. (2007) ‘Pojęcie administracji’ in Boć, J. (ed.) Prawo administracyjne. Wrocław: Kolonia Limited. Boć, J. (2011) ‘Konstytucja a prawo administracyjne’, Ruch Prawniczy, Ekonomiczny I Socjologiczny, 2, pp. 65–76. Dąbek, D., Zimmermann, J. (2005) ‘Decentralizacja poprzez samorząd terytorialny w orzecznictwie pokonstytucyjnym’ in Sarnecki P. (ed.) Samorząd terytorialny – zasady ustrojowe i praktyka. Warszawa: Wydawnictwo Sejmowe. Kancelaria Sejmu, pp. 7–42. Dolnicki, B. (2016) Samorząd terytorialny. Warszawa: Wolters Kluwer. Grzybowski, M. (2017) ‘Konstytucyjne zasady ustrojowe Rzeczypospolitej Polskiej’ in Posłuszny, J., Skrzydło, W., Eckhardt, K. (eds.) Ustrój polityczny Rzeczypospolitej Polskiej. Rzeszów: Rzeszowska Szkoła Wyższ, pp. 46–77. Grzybowski, M. (ed.) (2006) System rządów Rzeczypospolitej Polskiej. Założenia konstytucyjne a praktyka ustrojowa. Warszawa: Wydawnictwo Sejmowe. Knosala, E., Zacharko, L., Stasikowski, R. (2005) ‘Nowe zjawiska organizacyjnoprawne we współczesnej administracji publicznej’ in Podmioty administracji publicznej i prawne formy ich działania : studia i materiały z Konferencji Naukowej poświęconej Jubileuszowi 80-tych urodzin Profesora Eugeniusza Ochendowskiego.Tor u ń: Towarzystwo Naukowe Organizacji i Kierownictwa „Dom Organizatora”. Jakubowski, A. (2023) ‘Prezydent Rzeczypospolitej Polskiej jako organ administrujący (organ administracji publicznej)’, Państwo i Prawo, 2, pp. 3–32. Jackiewicz, A.I. (2008) Prawo do dobrej administracji jako standard europejski. Tor uń: Adam Marszałek. Jamróz, L., Ministrów, R., Rady, P. (2020) ‘Ministrów, administracja rządowa’ in Stanisław, B. (ed.) Prawo konstytucyjne. Białystok: Temida. Juchiewicz, J., Rady, P, Ministrów, R. (2012) Administracja rządowa w Polsce. Warszawa. Kmieciak, Z. (2023) ‘Prezydent RP jako organ administrujący a pojęcie jego prerogatyw’, Państwo i Prawo, 7, pp. 3–22. Król, P. (2014) ‘Stanowienie prawa przez administrację publiczną a zasada praworządności’, CASUS, 4, pp. 14–20. Kuciński, J. (2018) ‘Rada Ministrów in corpore jako organ kontrolowany przez Sejm – rozważania konstytucyjnoprawne. Część II. Działalność Rady Ministrów in corpore przedmiotem kontroli sejmowej’, Studia Prawnoustrojowe, 42, pp. 325–351 [Online]. Available at: https://doi.org/10.31648/sp.4950 (Accessed: 12 September 2024). Leoński, Z. (2004) ‘Ustrój i zadania samorządu terytorialnego’ in Wykrętowicz, S. (ed.) Samorząd w Polsce – istota, formy, zadania. Poznań: Wydawnictwo Wyższej Szkoły Bankowej. Mielczarek-Mikołajóws, J. (2020) ‘Prywatyzacja zadań publicznych w zakresie publicznego transportu miejskiego – zagadnienia wybrane’ in Blicharz, J., Raszewska-Skałecka, R. (eds.) Efektywność ekonomiczna jako cel prywatyzacji zadań z zakresu administracji świadczącej. Studium prawno-administracyjne. Wrocław: Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego. Modrzejewski, A. (2019) Komercjalizacja zadań jednostek samorządu terytorialnego w polskim systemie prawnym. Białystok: Temida 2. Pacak, M., Zmorek, K. (2013) Ustawa o wojewodzie i administracji rządowej w województwie. Komentarz. Warszawa: Wolters Kluwer. Pieprzny, S. (2023) ‘Wojewoda w systemie organów bezpieczeństwa i porządku p u b l ic z ne g o ’, Studia Prawa Publicznego, 41(1), pp. 31–47 [Online]. Available at: https://doi.org/10.14746/spp.2023.1.41.2 (Accessed: 12 September 2024). Princ, M. (2017) Standardy dobrej administracji w prawie administracyjnym. Poznań: Wydawnictwo Naukowe. Romaniuk, P. (2020) ‘Tradycje i przyszłość administracji publicznej w zakresie rozwoju e - u s ł u g ’, Journal Of Modern Science, 44(1), pp 269–284 [Online]. Available at: https://doi.org/10.13166/jms/125598 (Accessed: 12 September 2024). Sarnowiec-Cisłak, M. (2013) ‘Skutki wyroków TK dla oceny zdarzeń administracyjnoprawnych’ in Bernatt, M., Królikowski, J., Ziółkowski, M.(eds.) Skutki wyroków Trybunału Konstytucyjnego w sferze stosowania prawa. Warszawa: Wydawnictwo Trybunału Konstytucyjnego, pp. 41–54. Sarnecki, P. (2002) ‘Zakres działania i funkcje Rady Ministrów’ in Ministrów, R. (ed.) Organizacja i funkcjonowanie. Kraków: Kantor Wydawniczy Zakamycze, pp. 181–254. Sokołowski, A. (2016) ‘Kompetencje i zadania Prezesa Rady Ministrów i Rady Ministrów w ramach polityki bezpieczeństwa’, Świat Idei i Polityki, 15(1), pp. 209–231. Stasikowski, R. (2019) Pluralizm administracji publicznej. Warszawa: C. H. Beck. Stolicki, D. (2019) ‘Ustrój terytorialny’ in Bankowicz, M., Kosowska-Gąstoł, B. (eds.) Systemy polityczne. Podręcznik akademicki. Tom1. Zagadnienia teoretyczne. Kraków: Wydawnictwo Uniwersytetu Jagiellońskiego. Sześciło, D., Jakubek-Lalik, I. (2014) Administracja i zarządzanie publiczne. Nauka o współczesnej administracji. Warszawa: Stowarzyszenie Absolwentów Wydziału Prawa i Administracji Uniwersytetu Warszawskiego. Tuleja, P. (2021) ‘Art. 36.’ in Czarny, P., Florczak-Wątor, M., Naleziński, B., Radziewicz, P., Tuleja, P. (eds.) Konstytucja Rzeczypospolitej Polskiej. Komentarz. 2nd edn. Warszawa: Wolters Kluwer. Wierzbowski. M. (ed.) (2011) Prawo administracyjne. Warszawa: LexisNexis. Woś, T. (2003) ‘Czy dwuinstancyjne sądownictwo administracyjne realizuje konstytucyjną zasadą prawa do sądu?’ in Filipek, J. (ed.) Jednostka w demokratycznym państwie prawa. Bielsko-Biała: Wyższa Szkoła Administracji. Zacharko, L. (2013) ‘Konstrukcja uprawnień Prezydenta RP ze szczególnym uwzględnieniem uprawnień o charakterze administracyjnoprawnym’ in Zacharko, L., Dolnicki, B., Gołuch, A., Gronkiewicz, A., Józef, J.M., Wartenberg-Kempka, B., Ziółkowska, A., Zacharko, L., Glumińska-Pawlic, J., Żołnierczyk, E. (ed.) Organizacja Prawna Administracji Publicznej. Katowice: Wydawnictwo Uniwersytetu Śląskiego / Uniwersytet Śląski w Katowicach (UŚ). Zdyb, M. (2017) ‘Konstytucyjne podstawy ładu publicznego w administracji w świetle Konstytucji oraz orzecznictwa. Zagadnienia wybrane’, Annales Universitatis Maria e Curie – Skłodowska, 64(1), pp. 41–61 [Online]. Available at: https://doi.org/10.17951/g.2017.64.1.41 (Accessed: 12 September 2024). Zimmermann, J. (2006) ‘Prawo do sądu w prawie administracyjnym’, Ruch Prawniczy, Ekonomiczny I Socjologiczny, 68(2), pp. 307–322. Zimmermann, J. (2012) Prawo administracyjne. Warszawa: Wolters Kluwer Legal Sources Judgment Woivodeship administrative court in Poznan, 30.03.2022 r., sygn. III SA/Po 1608/21. Judgment Constitutional Court 20.05.2009 r., sygn. akt Kpt 2/08. Judgment Constitutional Court 26.02.2003 r., K 30/02, OTK-A 2003, nr 2, poz. 16.